1975
DOI: 10.1149/1.2134240
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transformations of the PbO2 Active Material during Cycling

Abstract: A combined optical and scanning electron microscope study of the PbSO4/PbO2 electrode has revealed changes in the PbSO4 crystallography and the tendency of PbO2 to form a network during life cycle tests. It was found that during cycling a definite coralloid structure developed. The mode of deposition and crystal form of the PbSO4 crystals changed with increasing cycle life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Therefore, the reduction charge of PbO 2 formed at 1.7 and 1.8 V in the Mn-containing electrolyte and the regarding effect of manganese could not be measured precisely. However, comparing peak C1 in the voltammograms of Figure 16indicates Simon et al 40 showed that a small amount of PbO 2 is usually found within the lead sulfate after the discharge process. However, it can be assumed that this PbO 2 amount is negligible compared to the amount of PbO 2 reduced during the potential scan.…”
Section: Potentiostatic-lsv Studiesmentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, the reduction charge of PbO 2 formed at 1.7 and 1.8 V in the Mn-containing electrolyte and the regarding effect of manganese could not be measured precisely. However, comparing peak C1 in the voltammograms of Figure 16indicates Simon et al 40 showed that a small amount of PbO 2 is usually found within the lead sulfate after the discharge process. However, it can be assumed that this PbO 2 amount is negligible compared to the amount of PbO 2 reduced during the potential scan.…”
Section: Potentiostatic-lsv Studiesmentioning
confidence: 83%
“…Although a small portion of PbO 2 might not be reduced during this peak, 40 peak III can be used to compare the amount of PbO 2 corrosion product formed on the anodes during the forward scan direction.…”
Section: Cyclic Voltammetry Studymentioning
confidence: 99%